Effect of sodium butyrate on gastric ulcer aggravation and hepatic injury inflicted by bile duct ligation in rats - Neveen A. Elnozahi; Esraa A. Said; Azza E. Bistawroos; Rania G. Aly (Elsevier, 2020)
Background and Aim: Cholestasis is positively associated with an increased risk of peptic ulceration. The present study investigated the aggravating effect of cholestasis on piroxicam-induced gastric ulceration. The study also evaluated the effect of sodium butyrate (SoB) on piroxicam-induced gastric ulceration in cholestatic animals and its effect on hepatic tissues and both effects were compared to ursodeoxycholic acid (UDCA) as a standard anticholestatic drug. Methods: Bile duct ligation was adopted for induction of cholestasis in rats. The cholestatic animals received saline, SoB (P.O, 400 mg/kg, twice daily) or UDCA (P.O, 30 mg/kg/day) for 4 days starting from the first day of surgery. On the 4th day, blood samples were collected for determination of serum hepatic markers, then gastric ulcers were induced by piroxicam administration (P.O, 50 mg/kg) and 4 h later, the stomach was isolated and gastric mucosa was collected for biochemical determinations. The ulcer indices for the investigated drugs were compared to omeprazole as a standard acid suppressive drug. Results: Piroxicam-induced ulceration was exacerbated in cholestatic rats. Gastric mucosa showed a significant elevation of MDA and TNF-α together with a significant decrease in GSH &VEGF levels. SoB treatment significantly attenuated ulcer development. The afforded protection was higher than that provided by UDCA and was not significantly different from that afforded by omeprazole. SoB significantly decreased gastric mucosal MDA and TNF-α level, whereas UDCA failed to alter these parameters. Both drugs significantly elevated GSH, VEGF and IL10 levels. Similar to UDCA, SoB showed a significant reduction in AST, ALT, GGT, ALP and bilirubin level. Histopathological examination confirmed the attenuating effect of SoB on gastric and hepatic injury. Conclusions: Sodium butyrate effectively protected gastric and hepatic tissues against cholestasis-induced damage. Gastroprotection was mediated through antioxidant, anti-inflammatory and angiogenic activities.